The role of adrenergic receptor polymorphisms in heart failure - Biolo,A. (2006)
The main function of the cardiac adrenergic system is to regulate cardiac work both in physiologic and pathologic states. A better understanding of this system has permitted the elucidation of its role in the development and progression of heart failure. Regardless of the initial insult, depressed cardiac output results in sympathetic activation. Adrenergic receptors provide a limiting step to this activation and their sustained recruitment in chronic heart failure has proven to be deleterious to the failing heart. This concept has been confirmed by examining the effect of ß-blockers on the progression of heart failure. Studies of adrenergic receptor polymorphisms have recently focused on their impact on the adrenergic system regarding its adaptive mechanisms, susceptibilities and pharmacological responses. In this article, we review the function of the adrenergic system and its maladaptive responses in heart failure. Next, we discuss major adrenergic receptor polymorphisms and their consequences for heart failure risk, progression and prognosis. Finally, we discuss possible therapeutic implications resulting from the understanding of polymorphisms and the identification of individual genetic characteristics.